Comparing the Efficacy of Microscopic Tympanoplasty (MT) and Endoscopic Tympanoplasty (ET) For Tympanic Membrane and Middle Ear Surgery: Microscopic Versus Endoscopic Tympanoplasty - Bhatti, Sanaullah; Irfan, Amber; Ashraf, Intasar; Bashir, Muhammad Mohsin; Saeed, Hassan; Javaid, Saman (Pakistan Journal of Health Sciences, 2025)
Endoscopic tympanoplasty and microscopic tympanoplasty is performed to restore hearing. But ET superior to MT as it less invasive. Objective: To evaluate the comparative efficacy of endoscopic tympanoplasty vs microscopic tympanoplasty for middle ear and tympanic membrane surgery. Methods: A prospective, quasi-experimental study was conducted in the ENT and Surgical Department of Bakhtawar Amin Memorial Trust Hospital, Multan from 15th October 2024 to 15th May 2025. A total of 100 adult patients undergoing type 1 endoscopic tympanoplasty or microscopic tympanoplasty were selected for the study by convenience sampling. Preoperative and postoperative air conduction, air bone gap and bone conduction were measured by pure tone. Picture archiving and communication system was used to perform preoperative speech audiometry to measure the perforation size. Results: The average surgery duration in endoscopic group was 79.23 ± 11.97 minutes and in microscopic group was 93.05 ± 19.81, which was significantly longer than the former (p<0.001). The length of hospital stay was also significantly short in endoscopic group (4.44 ± 1.11 min) due to less postoperative pain and minimally invasive procedure than microscopic group (8.09 ± 1.27 min) (p<0.001). On follow up, 5 (10%) patients in endoscopic group and 6 (12%) patients had a re-perforation (p=1.0). There was no significant difference between incidence of otorrhea (6% vs 12%, p=0.36) and pain (4% vs 2%, p>0.05). Conclusions: The audiological outcomes between type 1 endoscopic tympanoplasty and microscopic tympanoplasty were similar. However, surgical duration and length of hospital stay was better in endoscopic group.